Manajemen Kesehatan Mental Lansia Berbasis Dukungan Sosial di Panti Sosial Tresna Werdha Nirwana Puri - Shafa Nastiti Lestari; Nino Adib Chifdillah; Bernadetha Bernadetha (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Mental health is an important aspect in maintaining the quality of life of older adults, especially those living in social care institutions. Older adults in social institutions face various psychosocial challenges that may affect their mental condition, therefore appropriate mental health management is needed. Social support is one of the factors that plays an important role in mental health management among older adults. This study aimed to describe social support–based mental health management among older adults in Social Care Institution Tresna Werdha Nirwana Puri Samarinda. This study employed a qualitative approach with a descriptive design. The informants consisted of older adults and related parties in the social institution, selected using purposive sampling. Data were collected through in-depth interviews, observation, and documentation. Data were analyzed using thematic analysis, and data validity was ensured through source and technique triangulation. The results showed that mental health management among older adults was carried out through adaptation to the institutional environment, participation in social activities, and acceptance of their conditions. Social support from caregivers and fellow residents played an important role in helping older adults manage emotions, reduce feelings of loneliness, and enhance a sense of safety and comfort. Social support serves as a fundamental basis for mental health promotion efforts among older adults in social care institutions. This study concludes that social support–based mental health management is a relevant approach that should be strengthened in social care institution management.